Transfer Pengetahuan Tari Tradisional Minangkabau di Unit Kegiatan Kesenian Universitas Negeri Padang - Gilliani, Nakita Inge; Erlianti, Gustina (YASIN, 2024)
This research aims to describe how Minangkabau traditional dance knowledge transfer activities in the Arts Activity Unit of Padang State University using the knowledge transfer model of Liyanage et al. (2009). This research is a qualitative research with ethnographic method. The determination of informants in this study was carried out by snowball sampling method. Data collection was conducted using interviews and documentation. Data validation was done by triangulating sources and analysed through data reduction, data presentation, and conclusion drawing. The results of this study indicate that: (1) knowledge awareness of the creation of wave dance and plate dance at UKKES UNP arose because they considered that the previous work had been too long, so it was necessary to make a new dance work, after the last work more than 10 years ago; (2) knowledge acquisition is carried out by selecting advanced members who are then assigned to appreciate other works outside UKKES to broaden the members' insights; (3) knowledge transformation, the new insights they saw and recorded before, were discussed by both fields to start making new movements by the choreographer and new music by the composer; (4) knowledge associations that are applied during the work is realised through rehearsals between members for approximately 3 months, accompanied by evaluations after rehearsals to add or subtract both movements and music that have been made; and (5) knowledge application is the stage where the work has been completed and performed for the first time at Gesika 12 on 30th September 2023, and continues to be performed at other events both on campus and off campus.